2014
DOI: 10.1097/brs.0000000000000553
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physiological Loads on Cortical and Traditional Pedicle Screw Fixation

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
109
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(116 citation statements)
references
References 29 publications
1
109
0
6
Order By: Relevance
“…1,8 Some researchers have reported that CBT screw-rod fixation provided about the same stability as traditional PS-rod fixation, regardless of the presence of interbody support. 8 Others have reported that a CBT screw-rod construct has significantly superior resistance to craniocaudal toggling displacement compared with a traditional PS-rod construct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,8 Some researchers have reported that CBT screw-rod fixation provided about the same stability as traditional PS-rod fixation, regardless of the presence of interbody support. 8 Others have reported that a CBT screw-rod construct has significantly superior resistance to craniocaudal toggling displacement compared with a traditional PS-rod construct.…”
Section: Discussionmentioning
confidence: 99%
“…1,8 In addition, screw insertion through a caudomedial starting point enables less invasive posterior lumbar fixation by limiting dissection of the superior facet joints and reducing muscle dissection and retraction. Our cephalad screw trajectory follows a mediolateral-and caudocephalad-directed path according to the original method.…”
mentioning
confidence: 99%
“…Several studies have investigated factors influencing pedicle screw stability, such as trajectory (25,26), hole preparation (27), reuse of pilot holes (28) and screw back out (29). The removal of the cortex immediately surrounding the pedicle screw simulates a variation on screw placement known as hubbing.…”
Section: Discussionmentioning
confidence: 99%
“…Screw pull-out studies using human cadaveric tissues report a wide range of values from 102 to 1,741 N (15,26,28,(31)(32)(33)(34). Similarly, screw pull-out with the calf model reports values from 747 to 7,300 N, depending on treatment (30,35).…”
Section: Comparison To Existing Literaturementioning
confidence: 99%
“…In their report, CBT screws (average 4.5-mm diameter and 29-mm length) demonstrated a 30% greater uniaxial pullout strength and equivalent strength against toggle loading as compared to TT screws (average 6.5-mm diameter and 51-mm length) ( Table 1). More practically replicating a mechanism of pedicle screw loosening, Baluch et al compared the fixation strength of CBT screws (average 4.5-mm diameter and 32-mm length) with that of TT screws (average 6.5-mm diameter and 45-mm length) under cyclic loads perpendicular to the screw axis, and demonstrated the superior resistance of CBT screws 23) . Another study also evaluated the mechanical behavior of CBT screws in vivo by measuring insertional torque 24) .…”
Section: Fixation Strength Of Cbt Screwmentioning
confidence: 99%